PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA KELAS XI IPA SMA NEGERI 5 PEKANBARU - Diana, Mariaty Aprita; ', Erviyenni; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The application of active learning strategy instant assessment type to improve the students achievement on the subject of chemical equilibrium class XI science SMAN 5 Pekanbaru has been done. The research is a experiment research with pretest-posttest design. The population consisted of six classes grade. The sample were two classes, where class XI Science 2 as an experimental class and the class Xi science 3 as an control class. They were selected after normality and homogeneity test. Experimental class is a class that was applied to active learning strategy instant assessment type while the control class was not. Data analysis technique used is the t-test and gain normalized test. Based on data analysis obtained tcount > ttable (3,74>1,67), means that application of active learning strategy instant assessment type can improve student learning achievement on the topic of chemical equilibrium class XI Senior High School (SMA) 5 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,80. The category improvement of student achievement in control class was medium category with N-gain normalized is 0,54.Keywords :Learning Achievement, Active Learning Strategy Instant Assessment Type, Chemical Equilibriu.